Tourism marketing communication strategy at "dieng culture festival" as an effort to improve the economy of the dieng community - Heru Nugroho Aji (Enrichment : Journal of Management, 2023)
Technological advances and the times are able to erode the existence of local culture. Local culture is part of the tourism potential that can boost the economy. The Dieng Culture Festival is a successful cultural event and one that has the potential to boost the economy and expand employment opportunities in Indonesia. This research was conducted to find out how the marketing communication strategy was applied by the cultural performances of the Dieng Culture Festival. The research method used is descriptive qualitative method. The theory used in this research is marketing communication theory. The results found are that the marketing communication strategy is applied at four levels, namely individual level marketing communication, group level marketing communication, organizational level marketing communication, and mass level marketing communication. Good quality of human resource is a major component in the success of a marketing communications strategy. Mass media and social media are effective means of communication to promote the Dieng Culture Festival